Incorporating Biogeochemistry into Dryland Restoration. (5th May 2021) - Young, Kristina E; Reed, Sasha C; Ferrenberg, Scott; Faist, Akasha; Winkler, Daniel E; Cort, Catherine; Darrouzet-Nardi, Anthony
Abstract: Dryland degradation is a persistent and accelerating global problem. Although the mechanisms initiating and maintaining dryland degradation are largely understood, returning productivity and function through ecological restoration remains difficult. Water limitation commonly drives slow recovery rates within drylands; however, the altered biogeochemical cycles that accompany degradation also play key roles in limiting restoration outcomes. Addressing biogeochemical changes and resource limitations may help improve restoration efforts within this difficult-to-restore biome. In the present article, we present a synthesis of restoration literature that identifies multiple ways biogeochemical understandings might augment dryland restoration outcomes, including timing restoration around resource cycling and uptake, connecting heterogeneous landscapes, manipulating resource pools, and using organismal functional traits to a restoration advantage. We conclude by suggesting ways to incorporate biogeochemistry into existing restoration frameworks and discuss research directions that may help improve restoration outcomes in the world's highly altered dryland landscapes.